Factors and Impacts of Suboptimal Islamic Religious Education Lessons in Indonesia - Iqbal Ayyoby; Juliani; Amanda Kuslaina; Anisa Suge; Eva Marsela (Journal of Contemporary Islamic Primary Education, 2023)
Islamic Religious Education (IRE) is a crucial pillar in shaping the nation's character. However, in Indonesia, the implementation of IRE often falls short of expectations. This study aims to analyze the factors contributing to the suboptimal implementation of IRE and its impact on students. Using a qualitative-descriptive approach, the study identifies several key factors, including teacher quality, curriculum, facility support, and social environment. The consequences of these conditions include weak understanding of religious values, increased negative behavior among students, and limited student contributions to building a character-driven society. This study recommends strengthening policies, improving educator quality, and enhancing infrastructure as strategic measures.